Analysis of the Patriotic Health Movement in China: A Study on the Crude Health Movement. - Shan, Chonghe (International Journal of Social Sciences and Public Administration, 2024)
Due to multifaceted pressures encountered in developing countries, there exists significant resistance towards implementing public medical activities, particularly due to the contradictions arising from limited educational attainment. This paper commences by examining the patriotic health movement in China during the 1950s as a means of identifying solutions to these challenges. It initially reviews the difficulties faced by the Chinese government during the patriotic health campaign and explores potential remedies, subsequently assessing their applicability in contemporary times.  An analysis of public health responses in various developing nations over recent years reveals that many seemingly rudimentary approaches remain highly effective today.